Pulmonary gas exchange during exercise in young asthmatic patients. - Feisal, K A (1979)
Pulmonary function was examined in 19 young asthmatic patients at rest and during two levels of excercise. Findings at rest included decreased flow rates, increased residual volume, normal minute (VE) and alveolar (VA) ventilation, increased ratio of physiological dead space to tidal volume (VD/VT), increased alveolar-arterial oxygen tension difference (A-a PO2), and mild arterial hypoxaemia and desaturation. On exercise there was a normal increase in VE and VA, the VD/VT and the A-a PO2 decreased towards normal, and arterial oxygen tension improved, approaching normal levels. Significant acidosis did not develop.